Immobilization of Interfacial Activated Candida rugosa Lipase Onto Magnetic Chitosan Using Dialdehyde Cellulose as Cross-Linking Agent - Wang, Shushu; Li, Shan; Liu, Runtang; Zhang, Wei; Xu, Huajin; Hu, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Candidarugosa lipase (CRL) was activated with surfactants (sodium dodecyl sulfate [SDS]) and covalently immobilized onto a nanocomposite (Fe3O4-CS-DAC) fabricated by combining magnetic nanoparticles Fe3O4 with chitosan (CS) using polysaccharide macromolecule dialdehyde cellulose (DAC) as the cross-linking agent. Fourier transform infrared spectroscopy, transmission electron microscope, thermogravimetric analysis, and X-ray diffraction characterizations confirmed that the organic–inorganic nanocomposite support modified by DAC was successfully prepared. Enzymology experiments confirmed that high enzyme loading (60.9 mg/g) and 1.7 times specific enzyme activity could be obtained under the optimal immobilization conditions. The stability and reusability of immobilized CRL (Fe3O4-CS-DAC-SDS-CRL) were significantly improved simultaneously. Circular dichroism analysis revealed that the active conformation of immobilized CRL was maintained well. Results demonstrated that the inorganic–organic nanocomposite modified by carbohydrate polymer derivatives could be used as an ideal support for enzyme immobilization.